Work-Life Balance as A Human Resource Retention Strategy - A Study on The Millennial Generation in Sharia Institutions - Abrar, Muhammad (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2026)
Work–Life Balance (WLB) has become a critical issue for millennial employees who prioritize flexibility, meaningful work, and personal well-being, while Islamic institutions continue to face challenges in retaining this generation. This study examines WLB as a human resource retention strategy for millennials in Islamic institutions by synthesizing existing evidence on millennial characteristics, work engagement, social support, flexible work environments, and their implications for job satisfaction and performance. Using a qualitative literature review with a descriptive–analytical approach, this study integrates prior empirical findings and conceptual frameworks to identify key retention mechanisms. The main contribution of this study lies in proposing a value-based WLB framework that aligns Islamic organizational principles with millennial work preferences, highlighting WLB as a strategic, not merely operational, retention tool. The findings indicate that adaptive work policies, supportive spiritual and emotional environments, and opportunities for continuous professional development significantly enhance millennial retention in Islamic institutions. This study recommends the institutionalization of holistic WLB policies, strengthened intergenerational communication, and periodic evaluation of employee satisfaction to foster a sustainable, loyal, and competitive workforce.